Photooxidation of Emissions from Firewood and Pellet Combustion Using a Photochemical Chamber - Rubio-Campos, M; Gramsch-Labra, E (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The main emission source in Central and Southern Chilean cities is biomass combustion from residential heating and cooking due to old combustion technologies that are still widely utilized. In order to improve our understanding of biomass burning pollution and how it ages in the atmosphere, emissions from a pellet and wood stoves were studied with the aid of a photochemical chamber. Firewood combustion is an inefficient process that produces higher chamber loading of primary emission (gases and particles) compared to pellets. When these emissions are exposed to UV irradiation secondary particles are formed. However, with both fuels the secondary particle concentration was negligible with regards to the primary initial particle concentration. Observations show that when the initial mass is the same, firewood combustion emissions are more rapidly oxidized compared to emissions from pellet combustion. Particle aging evolution inside the chamber was evaluated using fragment tracer signals, via the mass fractions f44 vs f43 and f44 vs f60 triangles plots. For the same UV irradiation time, it was found that primary particles emitted form from firewood combustion show a slower aging rate compared to those emitted from pellet combustion, but this is due to high primary loading from wood combustion. Particle aging observed inside the chamber was similar to that found it in ambient urban air of Santiago de Chile in spring of 2011, indicating that chamber measurements can be a good indicator for some atmospheric processes. Levoglucosan, a well-known tracer for biomass combustion was also studied. It was found that wood stoves yielded higher levels than pellet stoves. This is due to the higher fuel combustion efficiency in pellet stoves, which yield low levoglucosan levels, making it difficult to use it for evaluation of the impact of pellet emissions on pollution. © 2019 by the authors.